EFFECT OF ZEOLITE SPEADING FREQUENCY IN RELATED TO CONTROL HOUSING ENVIRONMENTAL QUALITY - Pattiselanno, Freddy; Randa, Sangle Y. (Jurnal Zeolit Indonesia, 2004)
The research was aimed to investigate the application of zeolite spreading frequency in related to control housing quality. In this study, three aspects of quality were observed namely housing temperature, litter temperature and litter humidity. The result indicated that spreading frequency was only significant effective in controlling litter humidity. Treatment of P3 significantly (P